Pengaruh 2-iP dan NAA terhadap Pertumbuhan Plantlet Anggrek Dendrobium Hibrida pada Tahap Subkultur - ADINDA RIZKI NURANA; GEDE WIJANA; RINDANG DWIYANI (Fakultas Pertanian Universitas Udayana, 2017)
The Effects of 2-iP and NAA on The Growth of Dendrobium Hybrid Plantlets of in Subculture. The research was conducted during period of May to October 2016 at The Laboratory of Plant Tissue Culture, Faculty of Agriculture, Udayana University. The research employed a completely randomized design with 9 treatments and 3 replicates. The treatment were ZA = MS + 1 ppm 2-iP + 0,00 ppm NAA; ZB = MS + 1 ppm 2-iP + 0,25 ppm NAA; ZC = MS + 1 ppm 2-iP + 0,50 ppm NAA; ZD = MS + 2 ppm 2-iP + 0,00 ppm NAA; ZE = MS + 2 ppm 2-iP + 0,25 ppm NAA; ZF = MS + 2 ppm 2-iP + 0,50 ppm NAA; ZG = MS + 3 ppm 2-iP + 0,00 ppm NAA; ZH = MS + 3 ppm 2-iP + 0,25 ppm NAA; ZI = MS + 3 ppm 2-iP + 0,50 ppm NAA. The result showed that treatment of 2-iP and NAA significantly affected number of leaves, length of leaves, total of fresh weight and oven dry weight of plantlet. The concentration of 2 ppm 2-iP and 0,00 ppm NAA was the best treatment for optimal growth for Dendrobium plantlet during subculture.